Mating calls of selected Sarawak toads (Amphibia: Anura: Bufonidae) - Muhammad Fadzil Amram,; Ramlah Zainudin,; Hasnizam Abdul Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The sound produced by the anurans including toads can be a survival strategy for the selection of fittest males by their conspecific females and a form of effective prezygotic mechanism. Most of the published works on anuran sound production were on true frogs or ranids, yet little is known about sound characteristics of toads. Here we describe the properties of mating calls from six selected toad species from six study sites in Sarawak. Males’ mating calls were recorded and analyzed using SoundRuler Acoustic Analysis ver 0.9.6.0. Call characteristic were subsequently compared for toad species differentiation. The results showed that each species differ in call characteristics, with pulsating note, rate of note repetition and pitch being the most apparent characters. The highest number of pulse notes belongs to Duttaphrynus melanostictus while Ansonia spinulifer exhibited highest pitch and rate of note repetition. These species’ differences in mating call characteristics provide an additional method for anuran species classification besides morphological and molecular DNA data. It is also a very useful guide during field survey as the sound is audible and identification can be made without the need of capturing the toads.